Organ Procurement Organizations’ Nurses Perception of humanization of the process of obtaining organs for transplant - de Faria Lima, Adriana Aparecida; Paes da Silva, Maria Júlia; Pereira, Luciane Lúcio (O Mundo da Saúde, 2006)
The objective of this study was to identify the strategies used by nurses of organ capitation programs to humanize relations between the professionals, the family and potential organs donors. This was a descriptive research using a qualitative approach. Ten (10) semi-structured interviews were performed and tape-recorded, and data received analyzed were according discourse analysis principles. Two categories emerged: Providing total assistance to the donor and Providing total assistance to the family. Nurses takes humanizing donor care as offering total assistance to them, with a focus on the mechanical care for the body, allowing families to receive them with dignity; and regarding the family various strategies are cited that can humanize the process, such as continually offering information and explanations, allowing visits, speeding up the donation process, continuing to provide assistance to the family after the donation and also by continuing to care for the donors body after the donation. This study revealed a great concern nurses have regarding humanizing interpersonal relations with families as they understand this is a difficult and painful situation for them, and when they criticize the donation process they recognize how difficult it is to concretely use all the pointed strategies.